Transforming conventional mango orchard to high-density planting for high productivity and quality mango production - Srivastava, K. K.; Kumar, Dinesh; Shukla, P. K. (Indian Horticulture, 2024)
Malihabad is a famous ‘Dashehari’ mango growing region of Uttar Pradesh and exports mango to various parts of India as well as outside countries. Mango is traditionally grown at 10-12 m distance accommodating only 100-70 plants per ha resulting in large tree size and such trees starts late bearing. The high density planting system accommodates 8-10 times more trees/ha and bearing starts early, ultimately more income. Shri Vijay Kumar Shrotia, resident of Lucknow, started HDP planting of mango with technical support of CISH and earned R 1.5 to 2.0 lakh per ha in 3rd year and R 3.5-4.0 lakh/ha in 7th year. Due to small statured trees, harvesting of fruits and interculture operation are quite easy. CISH organized on-farm training and demonstrations for wider adoption of the HDP system.